The influence of class climate, school culture and literacy on green skills vocational culinary practice - Inten Nurani; Kokom Komariah (Universitas Papua, 2025)
Skills in material management and procedures are important to reduce food waste in the culinary field. SMK Tata Boga is required to form graduates who have green skills. However, initial observations show that the application of green skills in vocational schools is not optimal. This study aims to determine how the application of green skills in vocational culinary learning practices, as well as the influence of classroom climate, school culture, and literacy on it. The study involved 170 students, with data collected through questionnaires and observation sheets. However, the t-test shows that classroom climate does not affect the application of green skills in vocational culinary practice learning with a p-value of 0.239 and t-value of 1.182, school culture affects the application of green skills in vocational culinary practice learning with a p-value of 0.023 and t-value of -2.292, and information literacy does not affect the application of green skills in vocational culinary practice learning with a p-value of 0.612 and t-value of 0.508. The F test with a p-value of 0.128 shows that simultaneously, classroom climate, school culture, and literacy have no effect on the application of green skills in vocational culinary practice learning. For future research, other factors should be added that can increase the application of students' green skills in learning culinary practices. The application of students' green skills also needs to be seen from habituation which is not limited to activities in schools but also families and community environments.